2022
DOI: 10.22141/1608-1706.6.17.2016.88617
|View full text |Cite
|
Sign up to set email alerts
|

Лікування «нещасливої Тріади» Плечового Суглоба

Abstract: ÂñòóïУперше тяжку травму плечового суглоба, що су-проводжувалась переднім вивихом плеча, повноша-ровим травматичним ушкодженням ротаторної ман-жети та периферичних нервів у 1991 році описали Gonzalez і Lopez. В 1994 році таку комбінацію було названо «нещасливою», або «жахливою тріадою» плечового суглоба [9].Під «нещасливою тріадою» плечового суглоба розу-міють комбінацію вивиху плеча, як правило передньо-го або нижнього, масивного повношарового розриву ротаторної манжети плеча (РМП), включаючи варіант відривно… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Seddon et al classified nerve injuries as neuroapraxia, axonotmesis, and neurotmesis, with neurotmesis leading to complete functional loss and the need for surgical intervention [21,22]. Specifically for the shoulder terrible triad injury pattern, Strafun et al proposed a conservative approach, especially for the nerve injuries preserving 30% of nerve conduction during preoperative EMG [23]. One mechanism of nerve injury proposed is the crushing of the humoral head in the axillary border, but the mechanism of traction of the brachial plexus and distal nerves prevails, with the position of the limb during the accident affecting the nerves injured [24].…”
Section: Nerve Lesionsmentioning
confidence: 99%
“…Seddon et al classified nerve injuries as neuroapraxia, axonotmesis, and neurotmesis, with neurotmesis leading to complete functional loss and the need for surgical intervention [21,22]. Specifically for the shoulder terrible triad injury pattern, Strafun et al proposed a conservative approach, especially for the nerve injuries preserving 30% of nerve conduction during preoperative EMG [23]. One mechanism of nerve injury proposed is the crushing of the humoral head in the axillary border, but the mechanism of traction of the brachial plexus and distal nerves prevails, with the position of the limb during the accident affecting the nerves injured [24].…”
Section: Nerve Lesionsmentioning
confidence: 99%
“…However, if adequate RCT reconstruction does not cause the limb movement to improve, nerve function should be reassessed and operative treatment considered [17,18]. According to Strafun et al, if in preoperative EMG examination more than 30% of axillary nerve conduction is preserved, the patient should be operated-on for RCT and the treatment of neural injury should be conservative, but if conduction is less than 30%, early surgical exploration of axillary nerve is advocated [20]. Simonich et al concluded that the final functional result of the affected limb is more dependent on nerve recovery than on complete RCT repair [70].…”
Section: Accompanying Injuriesmentioning
confidence: 99%